Prevalence of musculoskeletal symptoms and associated risk factors among workers in the printing industry - Foong , May Chi (2012)
Musculoskeletal disorders (MSD) continue to be a major occupational safety and health issue in most industrialized countries and are a main cause of work- related disability and lost-time illnesses. Multiple risk factors could cause MSD. The relationship between occupational factors and MSD has been widely reported in different studies. The activities in the workplace such as repetitive movements, forceful exertion and prolonged standing or sitting posture known to be important MSD risk factors. In printing manufacturing, workers are directly exposed to the production process with job tasks requires heavy load lifting, carrying, pushing and the maintenance of awkward postures. For these reason, workers has a high probability associated with musculoskeletal symptom (MSS). In Malaysia, the printing industry is among the oldest and the top five largest industries in the manufacturing sectors. However, there is little information about the magnitude of the musculoskeletal problems and lack of assessment of working posture among the study population. Objective: This study aimed to identify the prevalence of musculoskeletal symptom (MSS) by body parts and to determine the relationship between socio-demographic, individual and occupational factors with MSS among printing production line workers. Method: A cross-sectional study was carried out at printing manufacturing company in Klang Valley, Malaysia. Respondents were randomly selected and a total of 250 workers who met the inclusion criteria participated in this study. The socio-demographic information and MSS were obtained through Standardized Nordic Questionnaire (SNQ). The posture analysis was performed using Rapid Upper Limb Assessment (RULA) method. The data was analyzed by using Statistical Package of Social Science (SPSS) version 19.0. Result: The overall prevalence of MSS was 79.6% and the highest prevalence by body parts were the lower back (48.0%). 70.0% of workers recorded RULA score above 5. There were significant association between MSS with age (p=0.017), gender (p=0.030), job duration (p=0.020) and RULA scores (p<0.05). Multiple logistic regression analysis showed that the significant risk factors for MSS were gender (2.88, 95% CI 1.66-8.16), job duration (1.06,95% CI 1.01-1.12), RULA score 3 (6.00,95% CI 1.37-27.09), RULA score 4 (8.20, 95% CI 1.55-43.43), RULA score 5 (9.10, 95% CI 1.97-42.07), RULA score 6 (14.38, 95% CI 3.09-66.99) and RULA score 7 (25.85, 95% CI 5.07-131.91). Conclusion: The overall prevalence of MSS was relatively high in the printing industry population. Age, gender, job duration and RULA scores were associated with MSS. Effective prevention strategies are required to address MSD in this population in order to minimize the risk for MSD.